2014
DOI: 10.1515/pjap-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of memory on experienced pain during Virtual Reality analgesia

Abstract: Abstract:Virtual Reality (VR) technology can be applied during pain treatment, acting as an effective distractor from pain stimuli. In our paper we investigate how memory influences experienced intensity of thermal pain stimuli. An experiment (within subject design) was conducted on 35 students from various Wroclaw universities. A cold pressor test was used for pain stimulation. Participants were immersed in customized virtual environments, created for this particular study. The environments differed at the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Before conducting this study we had finished two experimental studies using the same display technology and the same virtual environments, where a non-VR control condition was included. Both of these studies have found the large and significant increase of pain tolerance in VR conditions comparing to the non-VR condition [11,22]. General pain alleviating effect of VR has also been supported by numerous studies done by others, using similar pain stimulation (a cold pressor test), and various hardware and software VR technologies [13,9,23].…”
Section: A Designmentioning
confidence: 84%
See 1 more Smart Citation
“…Before conducting this study we had finished two experimental studies using the same display technology and the same virtual environments, where a non-VR control condition was included. Both of these studies have found the large and significant increase of pain tolerance in VR conditions comparing to the non-VR condition [11,22]. General pain alleviating effect of VR has also been supported by numerous studies done by others, using similar pain stimulation (a cold pressor test), and various hardware and software VR technologies [13,9,23].…”
Section: A Designmentioning
confidence: 84%
“…These mechanisms are still not fully known, as well as parameters of Virtual Environment (VE) which contribute to pain alleviation. Several published studies tested various properties of VEs but failed to find significant differences in their effectiveness [8,9,10,11,12]. Mühlberger et al [8] studied the effect of VE content on hot/cold pain stimuli endurance.…”
Section: Introductionmentioning
confidence: 99%
“…The concept, “Pain is in the Brain ”, and the entire biopsychosocial model, is the basis of many of the treatments using cognitive behavioural approaches developed in patients with chronic pain. An example of these interventions are Vlaeyen's fear‐avoidance model of pain, 9 the use of gradual exposure such as graduated motor imaging, 10 or the use of immersive visual reality in the treatment of pain 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…An example of these interventions are Vlaeyen's fear‐avoidance model of pain, 9 the use of gradual exposure such as graduated motor imaging, 10 or the use of immersive visual reality in the treatment of pain. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation